Public Sector Audit Committees: A Behavioural Reflection - Thomas , Keith; Purcell , Aquinas J. (Journal of Law and Governance, 2015)
Australian public sector audit committees are part of a governance process (Farrar, 2008) and assist in the maintenance of reliable systems of financial and performance reporting and internal controls as well as enhancing the internal auditor’s independence to provide unfettered advice (Cameron 2008, 2004). The Australian National Audit Office in its analysis of processes and practices described public sector governance as ‘how an organisation is managed, its corporate and other structures, its culture, and the way it deals with its stakeholders’ (Australian National Audit Office 2003, p. 6).